2008
DOI: 10.1016/j.ejcts.2008.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A quarter of a century experience with sleeve lobectomy for non-small cell lung cancer☆

Abstract: Sleeve lobectomy is a safe and effective therapy for selected patients with NSCLC. Vascular procedures and the use of induction chemotherapy did not increase mortality and morbidity; otherwise, the use of preoperative radiotherapy is not recommended. Overtime trend showed a significant lower mortality in the last period. This emphasises the importance of a learning curve and encourages the performance of this procedure in experienced centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 19 publications
1
40
0
4
Order By: Relevance
“…Overall survival following SL for patients with NSCLC ranges from 39-53% at five years and 28-34% at ten years (4,5,12,16,18,19,23). SL is technically more demanding than PN, and the decision to select this procedure may be influenced by the surgeons' experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall survival following SL for patients with NSCLC ranges from 39-53% at five years and 28-34% at ten years (4,5,12,16,18,19,23). SL is technically more demanding than PN, and the decision to select this procedure may be influenced by the surgeons' experience.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of N2 significantly impairs long-term outcomes among sleeve lobectomies due to systemic recurrences (16)(17)(18). Furthermore, there were no difference in survival with N0 and N1 disease (17)(18)(19)(20). Comparison between parenchymasparing SL and PN for central T3 NSCLC with absence of N2 disease is the less discussed previously.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Similar results had been reported in the comparison between pneumonectomy and sleeve lobectomy. [11][12][13][14][15] Subgroup analysis had been done in only one study: Luzzi et al reported that no significant survival difference between pneumonectomy and lobectomy for patients with N1 stage NSCLC and level 11 lymph node involvement. 16) On the other hand, a pneumonectomy, especially a right one, includes a higher occurrence of postoperative complications compared to the lobectomy: poorer quality of life, cardiopulmonary dysfunction, and long-term complications.…”
Section: Discussionmentioning
confidence: 99%
“…Sir Clement Price Thomas is credited with the first bronchial sleeve resection performed for a carcinoid tumour in 1947 at the Brompton Hospital in London, UK. Allison, in 1952, performed a sleeve lobectomy for a lung carcinoma and, in 1955, Paulson and Shaw reported the first comprehensive review on the use of these techniques [1][2][3][4]. At that time, sleeve resections were considered compromised procedures indicated for patients who could not tolerate the pneumonectomy.…”
Section: Introductionmentioning
confidence: 99%